Temporal Course of Cerebral Autoregulation in Patients With Narcolepsy Type 1: Two Case Reports - Guo, Zhen-Ni; Sun, Xin; Zhao, Yingkai; Yan, Xiuli; Zhang, Ran; Wang, Zan; Yang, Yi (Frontiers in Neurology, 2019)
Cerebral autoregulation is the mechanism of maintaining constant cerebral blood flow despite the changes in arterial blood pressure. In the present two cases, cerebral autoregulation was impaired in patients with narcolepsy type 1, and both venlafaxine and fluoxetine may have the potential function to improve the impaired cerebral autoregulation. A relationship may exist between impaired cerebral autoregulation and neurological symptoms in patients with narcolepsy type 1.